Predictions on the Development Dimensions of Provincial Tourism Discipline Based on the Artificial Neural Network BP Model - Yang Yang; Jun Hu; Mu Zhang (Bulletin of Electrical Engineering and Informatics, 2014)
As the tourism industry has gradually become the strategic mainstay industry of the national economy, the scope of the tourism discipline has developed rigorously. This paper makes a predictive study on the development of the scope of Guangdong provincial tourism discipline based on the artificial neural network BP model in order to find out how the branch of tourism studies can better adapt to the development of the tourism industry. The research findings indicate that the BP model can be applied to the predictions of the scope of the tourism discipline and provide a quantitative basis for decision making with regard to the spatial layout and optimal allocation of the tourism discipline.